PENGEMBANGAN LKPD BERBASIS DISCOVERY LEARNING PADA TEMA PENGALAMANKU KELAS I SEKOLAH DASAR - Rani Ravika Dewi; Nurmairina, Nurmairina (Bajang Institute, 2024)
This development research aims to develop a product worksheet based on Discovery Learning with the theme